Building creative confidence in idea management processes to improve idea generation in new product development teams - Perez Garcia, Marta; Bolton, Simon (Cranfield University Press, 2013)
This is a scoping paper that aims to establish effective practices and key players in the domain of Idea Management. The paper defines Idea Management as the generation, evaluation and selection of ideas. The purpose of the paper is to map the current landscape of methodologies and tools in order to identify gaps and support the development of a framework to enhance creative confidence in idea management. The study has two key research questions: (i) what factors are influencing current idea generation practices and (ii) what tools and approaches exist for idea generation. This will help identify how creative confidence can influence the idea generation processes. Creative confidence is the capability to come up with breakthrough ideas, associated with the bravery to perform. If stimulated in the right way with a valuable framework, its impact on employees’ performance is significant in improving team members’ innovation performance and quality of ideas.
Keywords: creative confidence; idea management; creative performance